Effects of oxidation on humic-acid-enhanced gypsum scaling in different nanofiltration phases: Performance, mechanisms and prediction by differential log-transformed absorbance spectroscopy. (1st May 2021) - Lin, Dachao; Bai, Langming; Xu, Daliang; Zhang, Han; Guo, Tiecheng; Li, Guibai; Liang, Heng
Highlights: Effects of oxidation on HA-enhanced scaling in nanofiltration were investigated Short-term membrane fouling was continuously aggravated by increasing oxidation Long-term membrane fouling decreased after an initial increase with stronger oxidation Oxidation influenced membrane fouling by changing the content of carboxyl on HA DAS could predict certain short-term membrane fouling in nanofiltration Abstract: The aim of this study was to evaluate the effects of oxidation on humic-acid-enhanced gypsum scaling in different nanofiltration phases, including the short-term membrane flux behaviors and the long-term ones. On the basic of correlation analysis between the changing physicochemical properties of feed solution and membrane fouling, the inner mechanisms were revealed from aspects of bulk crystallization (interaction between humic acid and inorganic ions) and surface crystallization (compositions and morphologies of surface crystallization). Furthermore, the reliability of applicating differential log-transformed absorbance spectroscopy for predicting membrane fouling was also systematically evaluated. There was an upward trend in short-term membrane fouling with increasing dosage of NaClO, while long-term membrane fouling decreased after an initial increase. During short-term filtration, the enhanced combination between inorganic ions and the humic acid with stronger density of carboxyl groups, which was generated more easily under stronger oxidation conditions, favored the earlier appearance of flux decline. During long-term filtration, the size of bulk crystallization depended on the total content of carboxyl groups in feed solution. Both of them increased firstly and then decreased with increasing oxidation. The terminal fouling layer resistance also shared a similar tendency with them, because the deposition of bulk crystallization on membranes and the formation of dense scaling layer were the direct reasons for the long-term membrane fouling. Furthermore, the differential log-transformed absorbance spectroscopy was proven to be an efficient approach to predict short-term membrane fouling, especially in the wavelength range of 260 to 280 nm. This research could not only provide guidance on alleviating oxidation-enhanced membrane fouling in nanofiltration but also propose an efficient way to predict the membrane fouling which was influenced by the interaction between organic matters and inorganic ions. Graphic abstract: Image, graphical abstract